A Wide-Band Circularly Polarized Wide-Gap Antenna Loaded with a Y-Shaped Metal Strip for L-Band Application. (18th May 2015) - Kang, Chun-Ying; Lin, Shu; Zong, Hua; Zhao, Zhi-Hua; Zhang, Xue-Ying
Abstract : A wide-band circularly polarized wide-gap antenna loaded with a Y-shaped metal strip applied to L-band is proposed in this paper. The Y-shaped metal strip coupling motivates the wide gap to achieve wide-band circularly polarized radiation. Both the simulated results by CST Microwave Studio and the measured results indicate that the antenna impedance bandwidth (reflection coefficient less than −10 dB) and axial ratio bandwidth (AR < 3 dB) are 35.9% (1.1–1.71 GHz). The antenna produces a dual circularly polarized radiation with gain of 0.8–3.2 dBic. The equivalent current array model of the antenna is also presented, which well explains the radiation characteristics of the antenna. The introduction of the metal reflecting plate makes the antenna a directional one, whose gain is above 4 dBic within the band. This design enables the satellite communication for most frequency bands with high gain, which has a vast potential for future development.